Urban NH3 levels and sources in six major Spanish cities. (January 2015) - Reche, Cristina; Viana, Mar; Karanasiou, Angeliki; Cusack, Michael; Alastuey, Andrés; Artiñano, Begoña; Revuelta, M. Aranzazu; López-Mahía, Purificación; Blanco-Heras, Gustavo; Rodríguez, Sergio; Sánchez de la Campa, Ana M.; Fernández-Camacho, Rocío; et al.
Highlights: The spatial distribution of NH3 levels was investigated in six major Spanish cities. Seasonal differences in NH3 levels were not consistent among cities. The relationship between NH3 and vehicles/km 2, SO2, NO X and PM10 was assessed. Urban NH3 sources: traffic, biological, solid waste and wastewater plants, industry. Mitigation strategies on urban NH3 are important to meet limit values of PM mass. Abstract: A detailed spatial and temporal assessment of urban NH3 levels and potential emission sources was made with passive samplers in six major Spanish cities (Barcelona, Madrid, A Coruña, Huelva, Santa Cruz de Tenerife and Valencia). Measurements were conducted during two different periods (winter–autumn and spring–summer) in each city. Barcelona showed the clearest spatial pattern, with the highest concentrations in the old city centre, an area characterised by a high population density and a dense urban architecture. The variability in NH3 concentrations did not follow a common seasonal pattern across the different cities. The relationship of urban NH3 with SO2 and NO X allowed concluding on the causes responsible for the variations in NH3 levels between measurement periods observed in Barcelona, Huelva and Madrid. However, the factors governing the variations in A Coruña, Valencia and Santa Cruz de Tenerife are still not fully understood. This study identified a broad variability in NH3 concentrations at the city-scale, and it confirms that NH3 sources in Spanish urban environments are vehicular traffic, biological sources (e.g. garbage containers), wastewater treatment plants, solid waste treatment plants and industry. The importance of NH3 monitoring in urban environments relies on its role as a precursor of secondary inorganic species and therefore PM X . Further research should be addressed in order to establish criteria to develop and implement mitigation strategies for cities, and to include urban NH3 sources in the emission inventories.